(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
This article analyzes per capita spending, the results of which were revealed growth of this indicator in the period from 2009 – 2019. The author of the article proposed appropriate measures for the introduction of factors that affect the dynamics of the growth of average per capita spending of the population until 2025.